2019
DOI: 10.1017/thg.2019.70
|View full text |Cite
|
Sign up to set email alerts
|

Update on Osaka University Twin Registry: An Overview of Multidisciplinary Research Resources and Biobank at Osaka University Center for Twin Research

Abstract: The Osaka University Twin Registry was originally established as a registry of older twins but was subsequently expanded to include twins of all ages. The Center for Twin Research at Osaka University Graduate School of Medicine has been managing this registry, as well as collecting research information and bioresources from twin participants. Based on the resources, multidisciplinary research projects have been conducted in collaboration with researchers from institutions both inside and outside Japan. One of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Of the 54 imaging biobanks retrieved, 21 were population-based (38.9%) [9,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and 33 were disease-oriented (61.1%) . Most imaging biobanks were European (26/54, 48.1%), followed by American (20/54, 37.0%) biobanks, with the remaining ones being based in Asia (5/54, 9.3%), Oceania (2/54, 3.7%) and Africa (1/54, 1.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 54 imaging biobanks retrieved, 21 were population-based (38.9%) [9,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and 33 were disease-oriented (61.1%) . Most imaging biobanks were European (26/54, 48.1%), followed by American (20/54, 37.0%) biobanks, with the remaining ones being based in Asia (5/54, 9.3%), Oceania (2/54, 3.7%) and Africa (1/54, 1.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding a platform, studies suggested that a web‐based platform could be the best solution 23,25,29,45–48 . To ensuring creating a reliable platform, a registry system should be designed based on the specific requirements of each country.…”
Section: Discussionmentioning
confidence: 99%
“…39,[41][42][43][44] Regarding a platform, studies suggested that a web-based platform could be the best solution. 23,25,29,[45][46][47][48] To ensuring creating a reliable platform, a registry system should be designed based on the specific requirements of each country. These requirements are defined according to its facilities, knowledge, infrastructure, and budget.…”
Section: Discussionmentioning
confidence: 99%
“…Participants Thirty-nine healthy Japanese twin-pairs were recruited from the registry established by the Center for Twin Research at Osaka University 58,59 . Twenty-two pairs were MZ twins (15 female and 7 male pairs; mean age ± standard deviation [SD] = 26.0 ± 4.3 years), and 17 pairs were DZ twins (6 female-female, 4 male-male, and 7 female-male pairs; mean age ± SD = 26.6 ± 5.3 years).…”
Section: Methodsmentioning
confidence: 99%